The effects of printing parameters on the surface quality of metal composite by using fused deposition modeling - Sukindar, Nor Aiman; Md Azhar, Muhammad Afif; Abd Halim, Nor Farah Huda; Kamaruddin, Shafie; Sulaiman, Mohd Hafis (Solid State Technology, 2020)
Fused Deposition Modelling (FDM) is a three-dimensional (3D) printing method that uses a material in filament form to fabricate a product directly from a CAD design. The flexibility of the system has placed this technology as a popular choice among the users whereby with a single FDM machine, various types of building materials can be printed such as polymer, composite, and ceramic. However, FDM poses its drawback in terms of producing a good surface finish. This research examines the effect of several printing parameters on the surface quality of metal matrix composite, which is a combination of polylactic acid and copper by using a low-cost FDM-3D printer. From the analysis, it shows that the raster angle is the main factor that affects the surface finish of the printed parts, followed by layer thickness and bed temperature. This finding is essential in tuning the right printing parameters to achieve the desired surface finish